A study on the purification of native sea salt by elutriation - Dulay, Ceferino I. (1973)
The International Salt Company Process produces high-purity salt by recrystallizing rock salt whose impurity consists mainly of anhydrite. This research studies the feasibility of substituting rock salt with native sea salt which contains highly-soluble magnesium salt beside anhydrite. The method used in the study is to wash the salt with salt solution to remove most of the impurities. It was found that although the salt solution produced by dissolving crude sea salt is saturated with respect to sodium chloride, it is unsaturated with respect to magnesium salts so that magnesium is dissolved readily in this wash solution. Most of the anhydrite crystals are mixed with the finer sizes of salt crystals. Elutriation was studied as a means of carrying away the anhydrite. It was found that a relatively pure salt can be obtained. From a salt having a composition of 89% NaCL, the purity can be raised up to about 98%. The calcium content can be reduced from 1.29% to as low as 0.4% and magnesium from 1.64% to 0.14%